Analysis of the Mitochondrial Membrane Potential Using the Cationic JC-1 Dye as a Sensitive Fluorescent Probe - Sivandzade, Farzane; Bhalerao, Aditya; Cucullo, Luca (Bio-protocol, 2019)
In recent years, fluorescent dyes have been frequently used for monitoring mitochondrial membrane potential to evaluate mitochondrial viability and function. However, the reproducibility of the results across laboratories strongly depends upon following well validated and reliable protocols along with the appropriate controls. Herein, we provide a practical user guide for monitoring mitochondrial membrane potential in whole cells using a fluorescent cationic probe. The data analysis of mitochondrial membrane potential we provide is one associated with the impact of xenobiotics such as tobacco smoking on blood-brain barrier endothelial cells including both mouse primary (mBMEC) and a mouse-based endothelial cell line (bEnd3) in a side by side comparison.